Comparison of the intrinsic disorder propensities of the RuBisCO activase enzyme from the motile and non-motile oceanic green microalgae. Issue 1 (1st January 2016) - Sena, Lucia; Uversky, Vladimir N.
ABSTRACT: Green oceanic microalgae are efficient converters of solar energy into the biomass via the photosynthesis process, with the first step of carbon fixation in the photosynthesis being controlled by the enzyme ribulose-1, 5-bisphosphate carboxylase/oxygenase (RuBisCO), which is a large proteinaceous machine composed of large (L, 52 kDa) and small (S, 12 kDa) subunits arranged as a L8 S8 hexadecamer that catalyzes the formation of 2 phosphoglyceric acid molecules from one ribulose 1, 5-bisphosphate (RuBP) molecule and one of carbon dioxide (CO2 ) and that is considered as the most abundant protein on Earth. The catalytic efficiency of this protein is controlled by the RuBisCO activase (RCA) that interacts with RuBisCO and promotes the CO2 entrance to the active site of RuBisCO by removing RuBP. One of the peculiar features of RCA is the presence of functional disordered tails that might play a role in RCA-RuBisCO interaction. Based on their ability to move, microalgae are grouped into 2 major class, motile and non-motile. Motile microalgae have an obvious advantage over their non-motile counterparts because of their ability to actively migrate within the water column to find the most optimal environmental conditions. We hypothesizes that the RCA could be functionally different in the non-motile and motile microalgae. To check this hypothesis, we conducted a comparative computational analysis of the RCAs from the representatives of the non-motile ( Ostreococcus tauri ) and motile ( Tetraselmis sp. GSL018) green oceanic microalgae.